2023
DOI: 10.1001/jamanetworkopen.2023.7809
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anxiety or Depression and Long-term Mortality Among Survivors of Out-of-Hospital Cardiac Arrest

Abstract: ImportanceThe recent American Heart Association guidelines added a sixth link in the chain of survival highlighting recovery and emphasized the importance of psychiatric outcome and recovery for survivors of out-of-hospital cardiac arrest (OHCA). The prevalence of psychiatric disorders among this population was higher than that in the general population.ObjectiveTo examine the prevalence of depression or anxiety and the association of these conditions with long-term mortality among individuals who survive OHCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When looking at psychological sequelae, our results are very similar to a recent Dutch study including 2′345 ICU 1-year survivors, wherein approximately 18% of unselected medical ICU patients had evidence of new depressive symptoms, 14% had evidence of new symptoms of anxiety, and 6% of patients had evidence of new symptoms of PTSD 59 . This is of great clinical relevance, as cardiac arrest survivors with symptoms of anxiety and/or depression seem to have higher long-term mortality compared to those patients without psychological problems 19 . When comparing the health-related quality of life after cardiac arrest in the 5 dimensions of the EQ-5D-3L with the reference results of the Swiss general population, the biggest differences could be observed in the ‘mobility’ and ‘usual activities’ domain, whereas in the ‘pain/discomfort’, ‘anxiety/depression’ and self-care the results were very similar to the reference results from the Swiss general population 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at psychological sequelae, our results are very similar to a recent Dutch study including 2′345 ICU 1-year survivors, wherein approximately 18% of unselected medical ICU patients had evidence of new depressive symptoms, 14% had evidence of new symptoms of anxiety, and 6% of patients had evidence of new symptoms of PTSD 59 . This is of great clinical relevance, as cardiac arrest survivors with symptoms of anxiety and/or depression seem to have higher long-term mortality compared to those patients without psychological problems 19 . When comparing the health-related quality of life after cardiac arrest in the 5 dimensions of the EQ-5D-3L with the reference results of the Swiss general population, the biggest differences could be observed in the ‘mobility’ and ‘usual activities’ domain, whereas in the ‘pain/discomfort’, ‘anxiety/depression’ and self-care the results were very similar to the reference results from the Swiss general population 54 .…”
Section: Discussionmentioning
confidence: 99%
“…PICS is an important driver of premature mortality and can have substantial financial implications for patients and their families 16 18 . Physical, psychological, and cognitive long-term disabilities are well-known in cardiac arrest survivors 4 , 19 25 . In a previous study, our research group found evidence of PICS in 50% of survivors at 12 months of follow-up, with most impairments experienced in the physical domain 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59] Anxiety and depression are common emotional experiences for individuals navigating the complexities of serious illness and mortality. 60,61 Spiritual care interventions, such as utilizing spiritual pain assessment sheets, animal-assisted therapy, spiritual counseling, and cognitive-behavioral therapy, have demonstrated their effectiveness in alleviating these psychological burdens. These interventions help geriatric patients find solace, make sense of their circumstances, and develop inner strength and resilience.…”
mentioning
confidence: 99%